(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
he study of social skills is a research area in which cultural, as well as political and social history are intertwined. Within this ield, we can distinguish the speciic subject of the emergence, settling and impact of Freemasonry in Mexico during the last two centuries. In the present paper, the presence of such groups will be looked at in the state of Michoacán at the beginning of the independent period, through the “York” and “Scottish” lodges. Many members of renowned groups of political power used these lodges as a protest space. hey debated and manoeuvred around the organizational models that they considered suitable for Mexico from their respective individual and collective points of view and expectations. his paper presents a prosopographical outline of the most representative members of the federalist-liberal and centralist-conservative coalitions, which at the same time supported these lodges, even ater their formal ban by the federal government in the autumn of 1828. he study will emphasize their force correlations and their respective networks.